THE EFFECT OF CENTRIFUGATION AND ULTRAFILTRATION AS A PRELIMINARY TREATMENT AND PERFORMANCE OF REVERSE OSMOSIS MEMBRANES IN OLIVE OIL MILL WASTEWATER (OMW) - Coskun, Tamer; Demir, Neslihan Manav; Debik, Eyup (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2012)
This study focuses on the treatment of olive mill wastewaters using reverse osmosis membranes. Besides, the effect of centrifuging and ultrafiltration as preliminary processes were also investigated. Four reverse osmosis membranes were used to treat effluents from centrifuging only, and from centrifuging-ultrafiltration processes. Ultrafiltration was applied under 3 bars of pressure while 10, 15, 20, and 25 bars were used for reverse osmosis. All of the membranes used provided, more or less, the same and satisfactory levels of treatment. The highest chemical oxygen demand (COD) and conductivity removals obtained in the study were 96.9% and 96.6%, respectively. The highest flux was observed to be 22.9 L.m(-2).h(-1). The study results suggested that using ultrafiltration, following the centrifuging, as preliminary processes increased the membrane flux in reverse osmosis; however, both did not affect COD and conductivity removal efficiencies considerably.
Keywords: Centrifuging; olive mill wastewater; reverse osmosis; ultrafiltration; ANAEROBIC TREATMENT; FILTRATION; WASTEWATERS; ELECTROCOAGULATION; DETOXIFICATION; PRETREATMENT; COMBINATION; REJECTION; INDUSTRY; Environmental Sciences & Ecology